Examination of the impact of lignin sulfonate based structure chemicals on fresh and hardened concrete - Ekinci, Cevdet Emin; Ay, Sevil; Baykus, Nurdan; Ay, Adem (Pamukkale Univ, 2016)
In this study, the impact of the addition of lignin sulfonate based chemicals on the properties of fresh and hardened concrete were examined. For C25/30 and C20/25 target class concretes, cement and chemical additive amounts were constant; changes were made only to water and aggregate amounts. Compressive strength values of the concretes were taken on the 1st, 7th and 28th days. Increases of compressive strength values were observed on days 1, 7, and 28. In the 1st study, in which C25/30 strength class was targeted for Cem I 42.5 R type cement provided by firm CF1, it was revealed that a 10.8% decrease in mixed water amount may occur. In the 2nd study, in which C20/25 strength class was targeted for Cem II 32.5 N type cement provided by firm CF2, it was revealed that a minimum 8.1% decrease may occur. In conclusion, although changes to viscosity, heat and unit weight of fresh concrete are caused by usage of lignin sulfonate based chemicals, they had no adverse effect on compressive strength of the concrete in this study.
Keywords: Concrete; Lignin sulfonate; Cement; Viscosity; Concrete heat